The ocean inside - McMahan, Janna (New York : Kensington ; Godalming : Melia [distributor], 2010)
Emmett and Lauren have always been a team, working together to raise their two daughters. But lately, with all their attention focused on nine-year-old Ainslie, they barely notice as their older daughter, Sloan, drifts further away from them and toward a reckless path that could tear their family apart...
Keywords: Parent and child -- Fiction; Parent and child; Fiction